Multisystem inflammatory syndrome in children related to COVID-19: Data from a Mexican national referral children's hospital - Menchaca-Aguayo, Héctor; Alpizar-Rodriguez, Deshire; Ramos-Tiñini, Pamela; Faugier-Fuentes, Enrique (Frontiers in Pediatrics, 2022)
Objectives To describe characteristics of patients with the pediatric inflammatory multisystem syndrome, temporally associated with SARS-CoV-2 (PIMS-TS)/multisystem inflammatory syndrome in children (MIS-C) and to identify factors associated with admission to the pediatric intensive care unit (PICU) in the Mexican children without coronavirus disease 2019 (COVID-19) vaccination. Methods This was a cross-sectional study performed at Hospital Infantil de Mexico Federico Gomez, a referral children's hospital in Mexico. The study included all cases that met the criteria for PIMS-TS/MIS-C, unvaccinated, between March 2020 and January 2022. The primary outcome was the admission to PICU. Associations of PICU admission with demographic and clinical variables were estimated using logistic regression analyses. Results We identified a total of 90 cases, with a median age of 7.5 years old, 47 (52.2%) girls. A previously healthy status was recorded in 76 (85%) children. All patients had positive PCR, serology test, or COVID-19 exposure. PICU admission was reported in 41 (45.6%) children. No deaths were reported. Patients received as treatment only corticosteroids in 53.3% of the cases. In univariable analyses, baseline factors associated with PICU admission were older age, hypotension or shock, positive PCR test, hypoalbuminemia, elevated procalcitonin, ferritin, and lymphopenia. Age, shock at admission, and hypoalbuminemia remained independently associated in the multivariable analysis adjusted by gender and previously healthy status. Conclusion We found a high proportion of previously healthy children in patients with PIMS-TS/MIS-C in our center. Critical care attention was received by nearly half of the children. The main treatment used was steroids. Age, shock at admission, and hypoalbuminemia were factors associated with PICU admission.